Mathematical modelling of bacterial mercury resistance - Crossland, Richard J. (2015)
A mathematical model of mercury resistance was designed which describes the following reactions: the cellular uptake and volatilisation of Hg2+, binding of the DNA by the regulator, mer protein synthesis, and dilution of quantities by cell growth. A total of 66 biological experiments were then selected from the scientific literature from studies of Tn21 and Tn501 in E. coli at 37 °C. These experiments were repeated in the computer simulation and the information from their 489 data points was incorporated into the 16 parameters of the model using the Metropolis-Hastings algorithm.